Power Flow management among PV, BESS and Grid for EV Charging - Karki, Menaka; Kunwar, Dol Raj; Sharma, Bijay; Paudel, Sunil; Ojha, Tanka Nath (Technical Journal, 2019)
Electric Vehicles (EVs) are the cleanest means of transportation compared to the conventional vehicles. Unlike conventional vehicles, EVs do not depend on petroleum products and thus use of electric vehicle is going to dominate the transportation sector soon. The battery electric vehicles need charging stations for their battery to charge. The proposed topology focuses on power flow management for charging of EV loads. it proposes electric vehicle charging system in which vehicle owners are allowed to park their vehicle in the charging station and EVs are charged up to their desired SOC level. The proposed system promotes penetration of RES to a larger extent which minimizes the kwh cost of grid energy consumption, and hence generating significant economical revenue of the charging station. In this paper, charging station is modeled with PV, battery and grid, and power management strategies are proposed among them. Regulation of load sharing and prevention of mismatch between circulating currents supplied by power sources is implemented using fixed droop method. The trend of power demand by EVs in the charging station is estimated and matching between demand and supply is implemented. Energy storage system is used in order to support continuous power availability in the station. The simulations are successfully implemented to validate the effectiveness of the system and to demonstrate the load management system by the uncoordinated method of charging. The overall system is implemented by algorithm run in MATLAB/Simulink.